Arthropod Demography, Distribution, and Dispersion in a Novel Trap-Cropped Cotton Agroecosystem. Issue 1 (26th February 2021) - Hagler, James R; Thompson, Alison L; Machtley, Scott A; Casey, Miles T
Abstract: Vernonia [ Vernonia galamensis (Cass.) Less.] (Asterales: Asteraceae) was examined as a potential trap crop for the cotton ( Gossypium hirsutum L., Malvales: Malvaceae) arthropod complex. Four rows of vernonia were embedded within a 96-row cotton field. The abundance of true bug pests, true bug predators, and spiders were determined by whole-plant and sweep net sampling procedures during the early, middle, and late phases of the cotton-growing season. The census data showed that the arthropods had a strong preference for the vernonia trap crop throughout the cotton-growing season. The movement of the arthropods from the trap crop into cotton was also measured using the protein immunomarking technique as a mark–capture procedure. The arthropods inhabiting the vernonia trap crop were marked directly in the field with a broadcast spray application of egg albumin (protein) during each phase of the study. In turn, the captured specimens were examined for the presence of the mark by an egg albumin-specific enzyme-linked immunosorbent assay. Very few marked specimens were captured beyond the vernonia trap crop 1, 3, and 6 d after each marking event. The arthropods' strong attraction and fidelity to vernonia indicate that it could serve as a trap crop for cotton pests and a refuge for natural enemies.